How well do Engineering students retain core mathematical knowledge after a series of high threshold online mathematical test? - PRENDERGAST, MARK; Carr, Michael; Breen, Cormac; Faulkner, Fiona (My University, 2017)
In the Dublin Institute of Technology, high threshold core skills assessments are run in mathematics for third-year engineering students. Such tests require students to reach a threshold of 90% on a multiple choice test based on a randomized question bank. The material covered by the test consists of the more important aspects of undergraduate engineering mathematics covered in the first 2 years of the Honours degree programme and the 3 years of the Ordinary degree programme. Students are allowed to resit the assessment as frequently as required until they pass. In order to measure the effectiveness of such an exercise, a follow-up assessment was given to students on their first day of their fourth year. A comparison is made with the level of basic mathematical knowledge of these students on their first day in third year, exactly a year previously. For the majority of the students we see a significant decrease in the performance of the students from the beginning of third year to the beginning of fourth year. In addition, students were surveyed for their perception of both how much knowledge had been retained and how effective they felt that this approach had been. Overall the students felt positive about the process of online testing and that it would make it easier for them to regain this information in the future.
PUBLISHED
Keywords: Mathematics; Skills assessment; Engineering students; Diagnostic Testing; Mathematics Education